Financial services trade, capital flows, and financial stability - Masamichi Kono; Ludger Schuknecht (World Trade Organization (WTO), 1999)
This study argues that trade policies regarding financial services are an important - but typically neglected - determinant of capital flows and financial sector stability. Financial services trade liberalisation which promotes the use of a broad spectrum of financial instruments and allows the presence of foreign financial institutions whilst not unduly restricting their business practices, results in less distorted and less volatile capital flows, and promotes financial sector stability. The study finds significant evidence in favour of this claim through an empirical analysis of GATS commitments in 27 emerging markets. Even countries where the financial system is weak, and where immediate, full-fledged financial sector liberalisation is not advisable, can open up certain types of financial services trade, as such trade strengthens the financial system without provoking destabilising capital flows.
Keywords: F13; F30; G20; 330; Financial services; international trade; capital flows; financial stability; WTO